On the Corner of Models and Cure: Gene Editing in Cystic Fibrosis - Ensinck, Marjolein; Mottais, Angélique; Detry, Claire; Leal, Teresinha; Carlon, Marianne S. (Frontiers in Pharmacology, 2021)
Cystic fibrosis (CF) is a severe genetic disease for which curative treatment is still lacking. Next generation biotechnologies and more efficient cell-based and in vivo disease models are accelerating the development of novel therapies for CF. Gene editing tools, like CRISPR-based systems, can be used to make targeted modifications in the genome, allowing to correct mutations directly in the Cystic Fibrosis Transmembrane conductance Regulator (CFTR) gene. Alternatively, with these tools more relevant disease models can be generated, which in turn will be invaluable to evaluate novel gene editing-based therapies for CF. This critical review offers a comprehensive description of currently available tools for genome editing, and the cell and animal models which are available to evaluate them. Next, we will give an extensive overview of proof-of-concept applications of gene editing in the field of CF. Finally, we will touch upon the challenges that need to be addressed before these proof-of-concept studies can be translated toward a therapy for people with CF.